Genome-Wide Identification of Cyclic Nucleotide-Gated Ion Channel Gene Family in Wheat and Functional Analyses of TaCNGC14 and TaCNGC16 - Guo, Jia; Islam, Md Ashraful; Lin, Haocheng; Ji, Changan; Duan, Yinghui; Liu, Peng; Zeng, Qingdong; Day, Brad; Kang, Zhensheng; Guo, Jun (Frontiers in Plant Science, 2018)
Cyclic nucleotide gated channels (CNGCs) play an important role in the uptake of Ca2+ ions, particularly with respect to a variety of signaling processes associated with stress responses, including plant-pathogen interaction. However, little is known about the characteristics and the functions of CNGC family in common wheat (Triticum aestivum L.). In this study, we performed a genome-wide identification of CNGC family in wheat and analyzed the function of TaCNGC14 and TaCNGC16 during wheat-Puccinia striiformis f. sp. tritici (Pst) interaction. As described herein, we identified a total 47 TaCNGCs in wheat, classifying these genes into four major groups (I-IV) with two sub-groups (IVa and IVb). Sequence analysis revealed a conserved motif, including a PBC and “hinge” region, found among all wheat CNGCs. Under Pst infection, the transcript levels of TaCNGC14 and TaCNGC16 in group IVb showed significant induction in a compatible interaction, while a reduction in gene expression was observed in incompatible interactions. In addition, TaCNGC14 and TaCNGC16 expression was significantly influenced by exogenously applied hormones, suggesting a role in hormone signaling and/or perception. Silencing of TaCNGC14 and TaCNGC16 limited Pst growth and increased wheat resistance against Pst. The results contribute to our understanding of the feature of the wheat CNGC gene family and the mechanism of TaCNGCs during wheat-Pst interaction.